The use of Kinesio Taping in edema treatment after primary knee arthroplasty. A case study - Magdalena Sobiech; Maciej Kochman (Kazimierz Wielki University, 2020)
A knee joint is one of the most exposed to the degenerative injuries causing pain and reducing motion abilities. In case of ineffective conservative treatment and advanced degenerative changes, a patient may be referred for knee arthroplasty. This surgery is often followed by pain and limb edema. Postoperative treatment can be supported by the Kinesio Taping. This paper aims to present the Kinesio Taping as a supportive post-surgery pain and edema treatment after knee arthroplasty. The 67-year-old-patient has been treated conservatively for the last 7 years. Due to the deteriorating changes and increasing pain the patient had been referred for the left knee arthroplasty procedure. After the surgery, the patient was stable, therefore the standard post-surgery procedures were implied. On the 3rd day, the lymphatic technique of the Kinesio Taping was added. After the end of the therapy (10th day after the surgery) the tests have shown a significant decrease of subcutaneous tissue swelling, pain relief, and knee joint circumference reduction.